Solve the following equation, answer as a reduced, mixed number. Then place the correct number in the box provided.
12(x - 6) = 2(x - 9)

Question

Asked 1/22/2014 4:43:37 PM

Updated 1/22/2014 7:35:41 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by yeswey [1/22/2014 7:34:07 PM]

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

wheels926w|Points 10|

Question

Asked 1/22/2014 4:43:37 PM

Updated 1/22/2014 7:35:41 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by yeswey [1/22/2014 7:34:07 PM]

Rating

8

12(x - 6) = 2(x - 9)

12x - 72 = 2x - 18

10x = 54

x = 54/10 = 27/5 = 5 2/5 as a mixed number

12x - 72 = 2x - 18

10x = 54

x = 54/10 = 27/5 = 5 2/5 as a mixed number

Added 1/22/2014 7:35:41 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [8/14/2014 8:59:59 PM], Rated good by andrewpallarca

If F(x) = x² + 4x and G(x) = 2x + 2, find F(5) + G(6).
44
59
98

Question

Updated 8/14/2014 9:32:38 PM

1 Answer/Comment

5(2 + 3) ÷ 25 + 8 ÷ 4
2.25
3
12.6 **Weegy:** 1/5 (More)

Question

Updated 1/21/2014 4:02:37 AM

1 Answer/Comment

5(2 + 3) ÷ 25 + 8 ÷ 4 = 3

Added 1/21/2014 4:02:37 AM

This answer has been confirmed as correct and helpful.

Solve the following equation, answer as a reduced, mixed number . Then place the correct number in the box provided.
3(x - 2) + 4(2x - 6) = 6(x - 4) + 8(2x + 1) **Weegy:** 4(3 - 2x) = 15 12 - 8x = 15 -8x = 15 - 12 -8x = 3 x = -3/8 (More)

Question

Updated 1/22/2014 7:33:40 PM

1 Answer/Comment

3(x - 2) + 4(2x - 6) = 6(x - 4) + 8(2x + 1)

3x - 6 + 8x - 24 = 6x - 24 + 16x + 8

11x - 30 = 22x - 16

- 11x = 14

x = - 14/11 = - 1 3/11 as a mixed number

3x - 6 + 8x - 24 = 6x - 24 + 16x + 8

11x - 30 = 22x - 16

- 11x = 14

x = - 14/11 = - 1 3/11 as a mixed number

Added 1/22/2014 7:33:40 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [8/14/2014 8:59:21 PM], Rated good by andrewpallarca

Solve the following equation. Then place the correct answer in the box provided. Answer in terms of a mixed number.
7(2x + 6) = 1 **Weegy:** 16x^3 is the answer. (More)

Question

Updated 1/22/2014 7:30:26 PM

1 Answer/Comment

7(2x + 6) = 1

14x + 42 = 1

14x = - 41

x = - 41/14

x = - 2 13/14

14x + 42 = 1

14x = - 41

x = - 41/14

x = - 2 13/14

Added 1/22/2014 7:30:26 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [8/14/2014 8:59:07 PM], Rated good by andrewpallarca

Negative charges repel other negative charges.
True
False

Question

Updated 1/23/2014 10:05:41 PM

1 Answer/Comment

Negative charges repel other negative charges.

This is True

This is True

Added 1/23/2014 10:05:41 PM

This answer has been confirmed as correct and helpful.

37,070,939

questions answered

There are no comments.